Rezonans . biuletyn informacyjny, no. 19, 1981 - NSZZ "Solidarność" "Telkom Teletra", [ed. Elżbieta Mińska et al.] (NSZZ "Solidarność" "Telkom Teletra", 1981)
Creation and circulation: For organizational use